Ser cristão no século IV: identidade na história eclesiástica de Eusébio de Cesareia. - Medeiros, Edalaura Berny (2012)
Cause the lack of cultural ties observed in the other religions of his times, Eusebius engages in a pioneering work to give Christians a sense of belonging through the research on the history of Hebrew and Jewish dissidents who followed Jesus Christ, which, according to Eusebius, represent the continuation of the legitimate religion of the patriarchs. The work becomes more complex when the author begins the narrative of the events of his contemporary times, which make up the second part of his work Ecclesiastical History. Through this work, we intend to show that Eusebius used examples of Christians and pagans for the narrative of the events he witnessed and that this choice gave contradictions to the his presentation, which were remedied by the logic of his speech, which didactical proposal makes that the message of reinforcement ofChristian identity, through the logic of identity shaping by binary opposition, justifies inadequacies, contradictions and even omissions